Feasibility Analysis of the Attractiveness of Lake Ngade Tourism in Ternate City, North Maluku - Betly Taghulihi; Vidhia Agmareina Hirto (Faculty of Economics and Business, University of Mataram, 2025)
This study analyzes the feasibility of the natural tourism attraction of Danau Ngade in Ternate, Indonesia, by evaluating eight key criteria: attractiveness, accessibility, accommodation, visitor facilities, market potential, clean water availability, environmental conditions, and management quality. A descriptive–exploratory qualitative approach was employed, supported by a scoring technique based on the modified ODTWA guidelines of the Directorate General of PHKA (2003) and the feasibility calculation formula by Putri et al. (2019). Data were collected through field observations, in-depth interviews, and documentation. The results show that Danau Ngade achieves an overall feasibility score of 78.898%, indicating that the destination is generally feasible and holds high development potential. Components such as attractiveness, accessibility, accommodation, visitor facilities, and environmental quality obtained high scores, demonstrating strong physical and ecological potential. However, the management, maintenance, and service components recorded low feasibility, highlighting weaknesses in organizational structure, service quality, and facility upkeep. The study concludes that while Danau Ngade has significant natural and market advantages, strengthening institutional capacity and improving service standards are essential to ensure sustainable development. These findings contribute to the understanding of feasibility assessment in small lake-based destinations and provide practical insights for improving tourism management and planning.